OVER 600 MILLION ADULTS ARE OBESE WORLDWIDE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, 14 June 2015 According to a World Health Organisation (WHO) report, worldwide, it is estimated that over 600 million people aged 18 years and older are facing the problem of overweight or obesity that leads to increased risk of cardiovascular disease, especially high blood pressure which has become the fifth leading cause of death in the world.